A literature review on work stress and audit quality reduction behavior: trend and future challenges - Prihantini, Febrina Nafasati; Januarti, Indira; Darsono, Darsono (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: This research aims to identify research development on work stress and its impact on audit quality reduction behavior.Design/Methodology/Approach: This qualitative study used the systematics of the PRISMA protocol review to analyze relevant articles.Research findings: Some research has focused more on the causes of job stress and audit quality reduction behavior. However, recent research has begun to harness the positive potential of auditors to reduce work stress and audit quality reduction behavior.Theoretical contribution/Originality: This study contributes to the literature review on work stress and audit quality reduction behavior.Practitioner/Policy implication: This review is expected to help organizations understand developments and findings related to work stress and audit quality reduction behavior, as well as support the development of effective stress management programs in the auditor's work environment.Research limitation/Implication: This literature review focuses only on the impact of job stress on audit quality reduction behavior. Nevertheless, it is still possible that work stress can also impact other aspects beyond audit quality reduction behavior, such as auditor performance and auditor judgment.